An investigation of scale effects on marine propeller under cavitating and non-cavitating conditions - Soydan, Ahmet; Bal, Sakir (Informa UK Limited, 2021)
In this study, scale effects on the hydrodynamic performance of DTMB 4119 propeller have been investigated in uniform flow under non-cavitating and cavitating conditions by a simple practical metho...